Analysis of Main Oil Pipeline Stress-Strain State During the Overhaul Operations - Zyma, Oleksandr; Pahomov, Roman; Farzaliyev, Sahib; Zhyhylii, Sergii (International Journal of Engineering and Technology, 2018)
The work is devoted to the actual problem of modernization and overhaul repairs of main pipelines sections after the structure individual elements exploitation period. Relevant spiral-seam pipes damages depending on the corrosion of the metal adjacent to the spiral seam and the pipeline insulation type were investigated. An analysis of the technological process features of connecting the pipeline existing parts with the newly parts was carried out. Factors that may lead to exceeding the permissible stresses and deformations of the steel main pipeline structure under the influence of non-operating loads and affect the reliability of the structure as a whole were detected. Evaluation and calculation of the steel main pipeline stress-strain state parameters with operational loads during the damaged pipeline area replacement were carried out in the article.Â Â